Striatal cholinergic dysfunction as a unifying theme in the pathophysiology of dystonia. (April 2015) - Eskow Jaunarajs, K.L.; Bonsi, P.; Chesselet, M.F.; Standaert, D.G.; Pisani, A.
Highlights: Cholinergic interneurons (ChIs) play a central role in striatal function. Impairment of ChIs produces dystonic movements. ChIs are paradoxically excited by dopamine D2 receptor agonism. Deficits in striatal synaptic plasticity are improved by muscarinic antagonists. ChI alterations may be a common endophenotype useful for investigations in dystonia. Abstract: Dystonia is a movement disorder of both genetic and non-genetic causes, which typically results in twisted posturing due to abnormal muscle contraction. Evidence from dystonia patients and animal models of dystonia indicate a crucial role for the striatal cholinergic system in the pathophysiology of dystonia. In this review, we focus on striatal circuitry and the centrality of the acetylcholine system in the function of the basal ganglia in the control of voluntary movement and ultimately clinical manifestation of movement disorders. We consider the impact of cholinergic interneurons (ChIs) on dopamine–acetylcholine interactions and examine new evidence for impairment of ChIs in dysfunction of the motor systems producing dystonic movements, particularly in animal models. We have observed paradoxical excitation of ChIs in the presence of dopamine D2 receptor agonists and impairment of striatal synaptic plasticity in a mouse model of DYT1 dystonia, which are improved by administration of recently developed M1 receptor antagonists. These findings have been confirmed across multiple animal models of DYT1 dystonia and may represent a common endophenotype by which to investigate dystonia induced by other types of genetic and non-genetic causes and to investigate the potential effectiveness of pharmacotherapeutics and other strategies to improve dystonia.